Variant selection in stationary shoulder friction stir welded Ti-6Al-4V alloy. Issue 1 (January 2018) - Jiang, Xiaoqing; Wynne, Bradley P.; Martin, Jonathan
ABSTRACT: Stationary shoulder friction stir welding of Ti-6Al-4V of 7 mm thickness was conducted with varying welding speeds and rotation speeds. Variant selection analysis was carried out based on the inherited α phase texture and the reconstructed β phase texture. The weld surfaces became significantly smoother with increasing welding speed and decreasing rotation speed. Heat input decreased greatly with increased welding speed and it decreased slightly with decreased rotation speed. The orientation relationship between the prior β grains was measured based on the reconstructed electron backscattered diffraction (EBSD) data. Weak Variant selection has occurred in all the welds because most of the prior β grains did not share {110} poles. Strong links between crystal orientation of the prior β grains and hardness have been found.